An assessment of microplastics threat to the marine environment: A short review in context of the Arabian/Persian Gulf. (July 2020) - Al-Salem, S.M.; Uddin, Saif; Al-Yamani, F.
Abstract: Microplastics are recognised as a (persistent) pollutant and are believed to be ubiquitous in the marine environment. The importance of this issue is evident from the large number of technical publications and research efforts within the past decade. However, the Arabian (Persian) Gulf region has few reported datasets in spite of being an area with excessive plastic use and a hefty generation rate of plastic solid waste. This communication aims at stimulating a discussion on this topic focusing on the available regional and international datasets, along with the environmental conditions that are likely to contribute to the disintegration and transport of the plastic debris rendering it as microplastic. This work also highlights some of the constraints in sampling techniques, identification methods, and the reported units of microplastics. Most studies employ neuston nets of variable dimensions that samples different thicknesses of surface water, which also posses a major constraint in standardising field sample collection. Extrapolation of a trawl to units such as particles.km −2 without considering the fact that neuston nets collect three-dimensional samples, is also another aspect discussed in this communication. This study also intends to initiate a discussion on standardising the practices across the region to enable an intercomparison of the reported data. In addition, it calls for a comprehensive assessment using the standardized methodology for putting a mitigation plan for microplastics as a potential threat detected in environmental sinks. Graphical abstract: Image 1 Highlights: A review of technical findings linked with microplastics, is conducted. The Arabian Gulf region is surveyed for microplastics sources. Plastic waste influence on the subject is studied. Evident link to primary (waste) and secondary (fragmentation) sources is discussed. Standardization in sampling techniques and results reporting is called for.